Development and Evaluation of Anti-Diabetic Potential of Polyherbal Formulations in Experimental Animals - DAHARWAL, PANKAJ MAHESH; MASKAWDE, MS. PRAJAKTA; BUNDELA, MS. RAGINI; SHUKLA, Dr. KARUNAKAR (International Journal of Multidisciplinary Research and Studies, 2023)
The current study used experimental animals to examine the polyherbal formulation's potential anti-diabetic effects. Using the wet granulation process, the polyherbal formulation in the form of granules was created. The produced granules underwent pharmaceutical evaluation. Beneficial effects of Polyherbal formulations were tested on diabetic rats induced with alloxan. Rats were given a single intraperitoneal injection of alloxan monohydrate (120 mg/kg) for 72 hours to develop diabetes. Following 72 hours of alloxan therapy for 11 days, the anti-diabetic effects of a polyherbal formulation were examined in diabetic rats induced with alloxan at two dose levels: 200 mg/kg and 400 mg/kg. The usual medication was Glibencamide at a dosage of 4 mg/kg. In diabetic rats, the polyherbal mixture demonstrated a decrease in blood glucose levels. It also reduces the treated groups' levels of triglycerides and cholesterol. The polyherbal mixture contains alkaloids, glycosides, saponin tannins, amino acids, and other ingredients, according to preliminary testing. α-amylase activity was responsible for the inhibitory activity. Blood glucose, serum triglycerides, and cholesterol were significantly increased (P < 0.01) in diabetic control. PHF treatment resulted in a significant (P < 0.05) drop in blood glucose levels when compared to diabetes control. PHF dramatically (P < 0.05) lowered the increased blood triglyceride and cholesterol levels. The outcome demonstrated the safety of the polyherbal formulation and its high level of anti-diabetic action.